SYNTHESIS OF ZrO2 VIA ULTRASONIC ASSISTED PRECIPITATION METHOD FOR PHOTODEGRADATION OF METHYLENE BLUE - Soni Setiadji; Nur Tursina; Nanda Dwimar Hakim; Sanusi Sanusi; Tety Sudiarti; Dani Gustaman Syarif (Jurnal Keramik dan Gelas Indonesia, 2021)
Zirconium dioxide (ZrO2) is a semiconductor material which its photocatalytic properties for degradation of methylene blue has been investigated in this research. ZrO2 was prepared from ZrCl4 solution by adding NaOH through precipitation method without ultrasonication, and also with ultrasonication for 1 h and 2 h. The specimens of ZrO2 were analyzed by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Brunauer-Emmett-Teller (BET). The XRD of all ZrO2 samples showed that the smallest ZrO2 crystal size was 8.149 nm based on Debye-Scherrer calculations for ultrasonic time of 2 h. The lattice parameter of ZrO2 under tetragonal phase was analyzed using Rietvield refinement by La Beil method. The specific surface area of all ZrO2 specimens were confirmed by BET. The result showed specific surface area of 99.741 m2/g for treatment with 2 h ultrasonication. The effect of ultrasonic assisted precipitation could increase the photocatalytic activity. This result showed that the degradation of methylene blue by ZrO2 with 2 h ultrasonication is higher than both by ZrO2 with 1 h ultrasonication and ZrO2 without ultrasonication with values of 93.00 %, 88.32 % and 77.53 % respectively, at 120 min irradiation, pH of 10 and 0.05 g of ZrO2